MELK mediates the stability of EZH2 through site-specific phosphorylation in extranodal natural killer/ T-cell lymphoma - Li, B.; Yan, J.; Phyu, T.; Fan, S.; Chung, T.H.; Mustafa, N.; Lin, B.; Wang, L.; Eichhorn, Pieter; Goh, B.C.; Ng, S.B.; Kappei, D.; et al. (AMER SOC HEMATOLOGY, 2019)
Oncogenic EZH2 is overexpressed and extensively involved in the pathophysiology of different cancers including extranodal natural killer/T-cell lymphoma (NKTL). However, the mechanisms regarding EZH2 upregulation is poorly understood, and it still remains untargetable in NKTL. In this study, we examine EZH2 protein turnover in NKTL and identify MELK kinase as a regulator of EZH2 ubiquitination and turnover. Using quantitative mass spectrometry analysis, we observed a MELK-mediated increase of EZH2 S220 phosphorylation along with a concomitant loss of EZH2 K222 ubiquitination, suggesting a phosphorylation-dependent regulation of EZH2 ubiquitination. MELK inhibition through both chemical and genetic means led to ubiquitination and destabilization of EZH2 protein. Importantly, we determine that MELK is upregulated in NKTL, and its expression correlates with EZH2 protein expression as determined by tissue microarray derived from NKTL patients. FOXM1, which connected MELK to EZH2 signaling in glioma, was not involved in mediating EZH2 ubiquitination. Furthermore, we identify USP36 as the deubiquitinating enzyme that deubiquitinates EZH2 at K222. These findings uncover an important role of MELK and USP36 in mediating EZH2 stability in NKTL. Moreover, MELK overexpression led to decreased sensitivity to bortezomib treatment in NKTL based on deprivation of EZH2 ubiquitination. Therefore, modulation of EZH2 ubiquitination status by targeting MELK may be a new therapeutic strategy for NKTL patients with poor bortezomib response.